EVALUASI IMPLEMENTASI KURIKULUM 2013 DI MADRASAH ALIYAH - Siskandar Siskandar (Center of Language and Cultural Studies, 2016)
This study describes success factors and obstacles of implementation of 2013 Curriculum at Islamic Senior Schools (Madrasah Aliyah). This study used qualitative approach. Data were collected using participatory observation, in-depth interview, Focus Group Discussion, and document analyses. Subject consisted of: school principal, vice principal, students, students’ parents, and school committee each of which was selected using snowball sampling techniques. Data were triangulated using process of checking, recheck and cross-check. The research revealed that: (1) success factors of implementation were: (a) completeness of curriculum infrastructure, (b) teacher competency, (c) principal leadership, (d) school facilities, (e) school environment and culture, and (f) effectiveness of monitoring and evaluation of curriculum inplementation; (2) obstacles of implementation included: false perception upon new 2013 curriculum, and shorts implementation on instructional design, classroom teaching, assessments, application of IT, teaching facilities and school management.